How Good Change Happens: The Political Economy of Child Nutrition. - Vaitla, Bapu. (2017)
Abstract: Although the political obstacles to child stunting reduction are formidable, some countries have indeed made important strides towards stunting reduction. In this study, I conduct a cross-country econometric analysis of the determinants of stunting reduction, and also look at reform experiences in Northeast Brazil and at the federal and state levels in India. The econometric analysis shows that income per capita and educational attainment are the most powerful determinants of stunting reduction, but find few other strong policy or political correlates; the results suggest that multiple pathways to stunting reduction exist, and few generalities apply across contexts. In Brazil, macroeconomic stabilization efforts and redistributive policies together drove stunting reduction, despite a lack of focus on child nutrition as such. In India, an elite/poor activist alliance, committed political leadership, and judicial activism helped bring about federal food and nutrition policy reforms. In the states of Kerala and Tamil Nadu within India, powerful class-based movements have permanently elevated the issue of access to basic health and nutrition services to political prominence. The overall message of the study is that improvements in a wide range of policy and political variables are likely necessary for poor countries to reach developed-world nutrition levels, but the determinants of marginal improvement at any given level are not consistent across political units. Though direct nutrition interventions (or food and health policies closely linked to nutrition) are not always politically feasible, other stunting reduction pathways may be available. Political opportunities vary by time and place, but skillful statecraft and a synergy of interests between the executive, judiciary, and civil society may provide enough political strength to overcome resistance to pro-poor, undernutrition-reducing public action.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Economics and International Business.; Advisor: Steven Block.; Committee: Peter Uvin, and Patrick Webb.; Keywords: Political Science, Economics, and International relations.